Business Management Strategies to Enhance MSME Competitiveness - Auliyaur Rokhim; Muh Ibnu sholeh (Cahaya Abadi Publisher, 2024)
This study aims to analyze the business management strategies employed by Micro, Small, and Medium Enterprises (MSMEs) in Pungpungan Village, Bojonegoro, with the goal of enhancing their competitiveness in the market. Utilizing a qualitative research approach, the study investigates the key factors influencing the success of local MSMEs and the challenges they face in a competitive market environment. Data was gathered through in-depth interviews with MSME owners, direct field observations, and document analysis, which focused on local government policies for MSME development. The results show that effective business management strategies adopted by successful MSMEs include product innovation, the use of digital marketing platforms, and the enhancement of human resource capacity through training and mentorship programs. Additionally, support from local governments and business communities has been identified as a vital factor in improving MSMEs’ access to capital and wider markets. Despite these positive strategies, the study also highlights significant challenges such as technological constraints, low levels of financial literacy, and difficulties in establishing a broad distribution network. These obstacles hinder the optimal growth and competitiveness of MSMEs. The research concludes that collaboration among government, academic institutions, and business actors is essential in creating a supportive ecosystem that ensures the sustainable growth of MSMEs. The findings of this study offer valuable insights for policymakers and can serve as a reference for formulating strategic policies aimed at enhancing the development of MSMEs, especially in rural areas.